꼬막(Tegillarca granosa)의 유전적 다양성 분석을 위한 드래프트 게놈분석과 마이크로새틀라이트 마커 발굴 - 김진무; 이승재; 조은아; 최은경; 김현진; 이정식; 박현; Kim, Jinmu; Lee, Seung Jae; Jo, Euna; Choi, Eunkyung; Kim, Hyeon Jin; et al. (한국해양생명과학회지, 2021)
The blood clam, Tegillarca granosa, is economically important in marine bivalve and is used in fisheries industry among western Pacific Ocean Coasts especially in Korea, China, and Japan. The number of chromosomes in the blood clam is known as 2n=38, but the genome size and genetic information of the genome are not still clear. In order to predict the genomic size of the T. granosa, the in-silico analysis analysed the genomic size using short DNA sequence information obtained using the NGS Illumina HiSeq platform. As a result, the genomic size of T. granosa was estimated to be 770.61 Mb. Subsequently, a draft genome assembly was performed through the MaSuRCA assembler, and a simple sequence repeat (SSR) analysis was done by using the QDD pipeline. 43,944 SSRs were detected from the genome of T. granosa and 69.51% di-nucleotide, 16.68% trinucleotide, 12.96% tetra-nucleotide, 0.82% penta-nucleotide, and 0.03% hexa-nucleotide were consisted. 100 primer sets that could be used for genetic diversity studies were selected. In the future, this study will help identify the genetic diversity of T. granosa and population genetic studies, and further identify the classification of origin between homogenous groups. 꼬막 종류 중 하나인 Tegillarca granosa는 해양 이매패류로서 한국, 중국, 일본 등의 중요한 수산 자원 중 하나이다. 꼬막의 염색체 수는 2n=38로 알려져 있지만, 유전체의 크기와 유전 정보에 대해서는 아직 명확하게 알려져 있지 않다. 꼬막의 유전체 크기 예측을 위하여 NGS Illumina HiSeq 플랫폼을 이용하여 얻은 짧은 DNA 서열 정보를 통하여 in silico 분석으로 유전체 크기를 분석하였다. 그 결과 꼬막의 유전체 크기는 770.61 Mb로 예측되었다. 이후 MaSuRCA assembler를 통하여 드래프트 게놈 조립 작업을 수행하고, QDD pipeline을 이용하여 SSR (simple sequence repeats) 분석을 수행하였다. 꼬막의 유전체로부터 43,944개의 SSR을 발굴하였으며, 다이-뉴클레오타이드(di-nucleotide) 69.51%, 트라이-뉴클레오타이드(tri-nucleotide) 16.68%, 테트라-뉴클레오타이드(tetra-nucleotide) 12.96%, 펜타-뉴클레오타이드(penta-nucleotide) 0.82% 그리고 헥사-뉴클레오타이드(hexa-nucleotide) 0.03%로 구성되었다. 이후 꼬막의 유전적 다양성 연구에 활용할 수 있는 100개의 마이크로새틀라이트 마커의 프라이머 세트를 선별하였다. 앞으로 이번 연구를 통해서, 꼬막의 집단유전학적 연구와 유전적 다양성을 규명하는데 도움이 될 것이며, 나아가 동종들 간의 원산지 분류를 알아낼 수 있을 것이다.